2020
DOI: 10.3389/fphar.2020.00074
|View full text |Cite
|
Sign up to set email alerts
|

Constituents and Metabolites of a French Oak Wood Extract (Robuvit®) in Serum and Blood Cell Samples of Women Undergoing Hysterectomy

Abstract: Ellagitannins are signature constituents of oak wood and their consumption has been associated with various health benefits. In vivo, they undergo metabolic degradation including gut microbial metabolism yielding urolithins. Only limited data is available about compounds being present in blood after intake of an extract from French oak wood, Robuvit ®. In the course of a randomized, double-blind, controlled clinical investigation, 66 patients undergoing hysterectomy received placebo or 300 mg Robuvit ® per day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Another limitation is that we did not control the dietary habits and treatment of patients after hysterectomy with antibiotics. This could influence the formation of different metabolites of Robuvit with different biological activities by different bacterial flora in individual patients [60]. To conclude, supplementation with Robuvit for 4 weeks improved convalescence of patients following hysterectomy, probably through its antioxidant activity as well as by the inhibiting of MMP-9 activity.…”
Section: Discussionmentioning
confidence: 90%
“…Another limitation is that we did not control the dietary habits and treatment of patients after hysterectomy with antibiotics. This could influence the formation of different metabolites of Robuvit with different biological activities by different bacterial flora in individual patients [60]. To conclude, supplementation with Robuvit for 4 weeks improved convalescence of patients following hysterectomy, probably through its antioxidant activity as well as by the inhibiting of MMP-9 activity.…”
Section: Discussionmentioning
confidence: 90%
“… 9 In a randomized, double-blind, controlled clinical study, the effect of Robuvit supplementation on patients undergoing hysterectomy was investigated. 5 Interestingly, the urolithin levels in patients consistently increased over 8 weeks of Robuvit supplementation, which suggests that a chronic intake of Robuvit can induce or amplify the gut bacteria responsible for the urolithin production, leading to an increase in the number of urolithin producers ( Fig. 3 ).…”
Section: Metabolism and Bioavailabilitymentioning
confidence: 91%
“…The reported improved mitochondria regeneration, enhanced ribosomal biogenesis, increased muscle mass, and the elevated antioxidant capacity caused by urolithins give a rational basis for the results of clinical trials with Robuvit, which was shown to accelerate overall energy. 8,[22][23][24] Decreased fatigue symptoms 22,23 and better sleep, 16,23,27 faster recovery after disease 7,[10][11][12]17,19,26 or surgery, 5,14 improved mood, 8,16,27 enhanced erectile function, 22,24 reinforced antioxidant defense mechanisms in periods of stress, 18 or enhanced muscle mass gain after intense exercise 6 are the effects that have been described in diverse clinical studies (Fig. 5).…”
Section: Clinical Effects Of Robuvitmentioning
confidence: 99%
See 2 more Smart Citations